Transformational Learning in Botswana: How Culture Shapes the Process - Sharan B. Merriam; Gabo Ntseane (Adult Education Research Conference, 2007)
Transformational learning as presented by Jack Mezirow has been critiqued for its Western, rational/cognitive orientation. This study was conducted in the African nation of Botswana and examined how that culture shaped the process. The TL experiences of 10 adults were constructed in terms of spirituality and the metaphysical world, community responsibilities and relationships, and gender roles.